Paul Yule (ed.), Late Antique Arabia: Ẓafār, Capital of Ḥimyar. Rehabilitation of a ‘Decadent’ Society. Excavations of the Ruprecht-Karls-Universität Heidelberg 1998–2010 in the Highland of the Yemen (Aethiopica, 2014)
Review
Keywords: Aksum; archaeology; excavation; Himyar; Ḥimyar; inscriptions; Kaleb; South Arabia; Yemen